2013
DOI: 10.1371/journal.pone.0059020
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Contribution of Paracine Effect versus Direct Differentiation on Adipose-Derived Stem Cell Transplantation Mediated Cardiac Repair

Abstract: BackgroundRecent studies have demonstrated that transplantation of adipose-derived stem cell (ADSC) can improve cardiac function in animal models of myocardial infarction (MI). However, the mechanisms underlying the beneficial effect are not fully understood. In this study, we characterized the paracrine effect of transplanted ADSC and investigated its relative importance versus direct differentiation in ADSC transplantation mediated cardiac repair.Methodology/Principal FindingsMI was experimentally induced in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
115
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(121 citation statements)
references
References 40 publications
(57 reference statements)
2
115
0
4
Order By: Relevance
“…Furthermore, a hypothesis of the current research is that enhanced myocardial repair is contingent on communication between injected stem cells and the cells within the heart. [12][13][14] This communication could come from secretion of cardioprotective factors (paracrine signaling) or from direct contact between stem cells and cardiomyocytes. Paracrine signaling between the donated stem cell population and host myocardium is important to promote cell-based myocardial repair.…”
mentioning
confidence: 99%
“…Furthermore, a hypothesis of the current research is that enhanced myocardial repair is contingent on communication between injected stem cells and the cells within the heart. [12][13][14] This communication could come from secretion of cardioprotective factors (paracrine signaling) or from direct contact between stem cells and cardiomyocytes. Paracrine signaling between the donated stem cell population and host myocardium is important to promote cell-based myocardial repair.…”
mentioning
confidence: 99%
“…However, the question of which mechanism is more critical for achieving therapeutic benefit remains unanswered. A recent report demonstrated that ASCs transplanted to the myocardium, post infarct, decreased infarct-associated cell death and stimulated reperfusion of damaged heart tissue [47]. These benefits were linked to angiogenic paracrine secretion of ASCs, rather than trans-differentiation into cardiomyocytes [47].…”
Section: Discussionmentioning
confidence: 99%
“…The use of CM for therapy is very appealing and may be booming in the near future, as studies on the use of CM for various diseases are accumulating [1, 333]. Conditioned medium contains various growth factors and tissue regenerative agents, which were secreted by the stem cells.…”
Section: Introductionmentioning
confidence: 99%